Ayurvedic management of vitiligo (Shvitra) - Meenakshi Sharma; Sisir Kumar Mandal (Journal of Ayurveda, 2021)
Introduction: Vitiligo is a common autoimmune disorder in which the destruction of melanocytes occurs, resulting in the formation of white spots on the skin. It has a major impact on the quality of life of patients, as they feel distressed and stigmatized by their condition. Treatment available in contemporary medicine has its own limitations and side effects. In Ayurveda, Shvitra is the term employed for the hypopigmentation disorders of the skin. Due to the holistic approach, Ayurveda has the vast potential to treat such autoimmune skin diseases. Here, a case study of chronic vitiligo treated successfully with ayurvedic interventions is reported. Main Clinical Finding: There were white patches measuring about 7x5 cm, 4x3 cm, 3x3 cm and 4x2 cm on right and left arm, neck, chest, forehead region respectively. There were multiple small patches on fingers of hand also. The spots and patches were asymmetric, well defined whitish-pink and without scaling and discharge. Diagnosis: The patches were spread on large area (bahala), colour of patches was white/whitish pink (tvaka vaivarnyata), no secretion from lesion (aparisravi) ,with no itching (kandu) and loss of hair (romavidhvamsha) on affected area, so the case was diagnosed as Shvitra kustha on the bases of observed sign and symptoms. Intervention: The management approach was personalized and holistic in nature incorporating Ahara,vihara and Aushadha. In Sanshamana chikitsa Pitta-kapha shamaka and Vyadhi pratyanika line of treatment including internal administration of Khadira sara, decotition of Amla and Udumbara Chhala and Shashilekha Vati with external application of Chakramarda beeja, Muli beeja and Vakuchi beeja lepa was incorporated. Outcome: After 3 months of interventions, skinny spots appeared between the white patches. After six months, patches of chest, neck and forehead almost disappeared and that of arms significantly decreased with no recurrence. No adverse effect was seen during treatment and in follow up period